1995
DOI: 10.1089/end.1995.9.487
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Nephrectomy: Animal and Human Anatomic Studies

Abstract: Retroperitoneal laparoscopic nephrectomy with CO2 insufflation was performed in 11 goats. The hemodynamic and blood gas repercussions of retroperitoneal laparoscopy were compared during the first 30 minutes with those induced by intraperitoneal laparoscopy. With the animal placed in the left lateral supine position, the hemodynamic and blood gas changes were similar with the two techniques and had a similar time course. The technical feasibility of retroperitoneal laparoscopy in animals was confirmed in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Guilloneau et al [25,26] and Mandrassi et al [21] have shown clearly, in pigs and human adult population, that this procedure does not carry any anesthetic risk. Hemodynamic changes and CO2 diffusion were identical with the two laparoscopic techniques, intra-and retro peritoneal.…”
Section: Introductionmentioning
confidence: 89%
“…Guilloneau et al [25,26] and Mandrassi et al [21] have shown clearly, in pigs and human adult population, that this procedure does not carry any anesthetic risk. Hemodynamic changes and CO2 diffusion were identical with the two laparoscopic techniques, intra-and retro peritoneal.…”
Section: Introductionmentioning
confidence: 89%